PENINGKATAN KETERAMPILAN MENYIMAK DENGAN MENGGUNAKAN MEDIA AUDIO PADA SISWA SEKOLAH DASAR - Mahpudoh, Mahpudoh; Romdhoningsih, Diana; Lutfiyah, Lutfiyah; Ain, Farhatul; Julina, Julina; Septiani, Dewi Syifa (Universitas Sultan Ageng Tirtayasa, 2023)
This research aims to improve students' listening skills using audio media using audio media, namely a model of using audio media such as playing learning material via cell phone speakers for students in grades V and VI at elementary school level. This research is classroom action research carried out in three cycles. In the learning process there are two stages, namely, the planning stage and the implementation stage. The subjects in the research were students in grades V and VI of Elementary School who carried out Tutoring (bimbel) at IC Private Tutoring (Iqro Corner) on Jl. KH. Abdul Latief No.47 Sumur Pecung, Serang City, Banten, 42118. The results of the study showed an increase in the average score of the final listening test after receiving treatment on the effectiveness of using audio media in each cycle.